The Study of Drag Reduction ability of Naturally Produced Polymers from Local Plant Source - Kaur, Harvin (2013)
Drag reduction is observed as reduced frictional pressure losses under turbulent flow conditions and hence, substantially increases the flowrate of the fluid. Practical application includes water flooding system, pipeline transport and drainage system. Drag reduction agent, such as polymers, can be introduced to increase the flowrate of water flowing, reducing the water accumulation in the system and subsequently lesser possibility of heavy flooding. Currently used polymer as drag reduction agents is carboxymethylcellulose, to name one. This is a synthetic polymer which will seep into the ground and further harm our environment in excessive use of accumulation. A more environmentally-friendly drag reduction agent, such as the polymer derived from natural sources or biopolymer, is then required for such purpose. As opposed to the synthetic polymers, the potential of biopolymers as drag reduction agents, especially those derived from a local plant source, are not extensively explored. The drag reduction of a polymer produced from a local plant source within the turbulent regime will be explored and assessed in this study using a rheometer where a reduced a torque produced can be perceived as a reduction of drag. This technique of assessment for drag reduction ability is also unique as many literatures on drag reduction rely heavily on flow loop data which sometimes, require time and high cost for the fabrication of the flow loop. The new method proposed is less time consuming and is more practical which is producing carboxymethylcellulose from the banana peel. The cellulose powder was converted to carboxymethylcellulose (CMC) by etherification process using sodium monochloroacetate and sodium hydroxide. The carboxymethylation reaction then was optimized against the reaction temperature. Then, the biopolymers will be rheologically characterized where the viscoelastic effects and the normal stresses produced by these biopolymers will be utilized to further relate and explain the drag reduction phenomena. The research is structured to focus on producing the biopolymer and also assess the drag reduction ability of the biopolymer produced. Various temperatures when synthesizing the biopolymers will be studied as a drag reduction agent to obtain the optimum value of which the biopolymer works the best. The rheological behavior of the biopolymers will also be analyzed and relate to the drag reduction ability. The results are intended to expand the currently extremely limited experimental database for biopolymers in turbulent flow.